Moral Necessities of Content Filtering and Refinement in Cyberspace - Hosein ali rahmati; Hamid shahriari (اخلاق وحیانی)
Ethically, the most important purpose of content filtering and refinement in cyberspace is to prevent the violation of moral principles. Achieving this purpose, however, requires that all practitioners of filtering be aware of their duties and responsibilities and do their best to realize them. But until these duties are not recognized and specified, it would be an absurd expectation that filtering serve the moral purposes and be implemented in a moral way. In this paper, the most important responsibilities of citizens and public authorities for filtering are introduced, the related challenges are analyzed, and some strategies are presented for decreasing them. Responsibilities include information-giving, supervision, avoidance of bypassing the filtering, companionship between users and related administrations, privacy and trust, and challenges include technical and human mistakes, the conflict between moral responsibilities, and weakness of motivation. For the convenience and clarification of the discussion, responsibilities are divided into two general categories of shared and dedicated ones. There are other related discussions in this paper like the definition of moral duty, its importance, and the source and foundation of commitment to moral duty. The methodology of the paper is analytical and it is for practical applications, and besides its philosophical analysis it uses the moral teachings of Islam.